2022
DOI: 10.1007/s12310-022-09502-9
|View full text |Cite
|
Sign up to set email alerts
|

The Contributing Role of Family, School, and Peer Supportive Relationships in Protecting the Mental Wellbeing of Children and Adolescents

Abstract: Globally, mental disorders are the leading cause of disability in children and adolescents. Previous research has demonstrated that supportive relationships are a key protective factor against poor mental health in children, particularly amongst those who have experienced adversity. However, fewer studies have examined the relative impact of different types of supportive relationships. The current study examined the association between level of family adult support, school adult support, and school peer suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Psycho-social measures are always considered by human beings and such measures involve preventive behavior as very significant for diseases and illnesses ( 48 ). For instance, Butler et al revealed how the level of awareness regarding respiratory infection and preventive behavior relates to the incidence of infection ( 17 ). Moreover, in the context of mental wellbeing, awareness and knowledge play a crucial role in developing preventive behavior among people ( 6 ).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Psycho-social measures are always considered by human beings and such measures involve preventive behavior as very significant for diseases and illnesses ( 48 ). For instance, Butler et al revealed how the level of awareness regarding respiratory infection and preventive behavior relates to the incidence of infection ( 17 ). Moreover, in the context of mental wellbeing, awareness and knowledge play a crucial role in developing preventive behavior among people ( 6 ).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In the case of improving mental wellbeing, the role of family support is quite significant, especially for students. Receiving family support from parents, siblings, or relatives improves outcomes, such as satisfaction, relived, and calmness, thus improving the overall mental wellbeing ( 17 ). Not only this, family support strengthens the relationship between family members which is integral to successful acculturation ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The school nurses described in this study the importance of training the adolescents in a language to speak about difficult feelings and thoughts and may be one of many prevent mental health problems or help them in the pathway in the help system ( World Health Organization, 2020 ). Fostering positive peer relationships in group interventions may promote mental health for all adolescents ( Butler et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration with teachers was described as important with teachers asking students, they wanted a second opinion to see the school nurse. Supportive teacher–student relationships may promote mental health ( Butler et al., 2022 ), with the school nurse as a collaborative partner giving the teachers the possibility to ask the student, they worry about, to see the school nurse. Frauenholtz et al (2017) claim that school staff have limited knowledge about children’s and adolescents’ mental health and thus do not recognize mental health problems in their students, a study conducted in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the UK by Butler et al (2022) , school sources of support had a protective effect on the mental well-being of children with low family support, indicating the crucial role that school resources can play in reducing symptoms of anxiety and depression among adolescents. In another study conducted by Escobar et al (2020) in Brazil, with a sample of 102,072 adolescents from public and private schools, psychological health issues were associated with some family contexts including family violence and relationships with parents.…”
Section: Introductionmentioning
confidence: 99%